Bioethics as respect and love of life: some reflections on Fritz Jahr's thought - Cheng-tek Tai, Michael (Journal international de bioéthique et d'éthique des sciences, 2016)
Humankind talks about ethics for a noble purpose of improving and enhancing human relationships toward one another. No ethics would be mentioned if care and concern for others do not exist. Obviously, the foundation of ethics is mutual caring among people. This concern however has been expanded to include all life forms on earth therefore a new term bioethics is coined. As Fritz Jahr said that we must respect every living being. Thus, what is bioethics? it is a respect and love of life.